Building the Independence of Islamic Religious Education Students Through Edupreneurship - Hunaida, Wiwin Luqna; Manan, Abdul; Hadiyansyah, Dhuha; Fahlehfi, Muhammad Ikbal; Firdaus, Muhammad Dhilal Mustambit (Jurnal Tarbiyatuna, 2024)
The concept of edupreneurship has emerged as a dynamic and transformative power in the field of education. The edupreneurs, with entrepreneurship mindset and spirit of education, are in a unique position to bridge the gap between traditional academics and rapidly growing global demands. This article tries to answer the problem of how edupreneurship strategies develop the independence of students of Islamic Religious Education Program of UIN Sunan Ampel Surabaya. Student independence indicates by the ability of financial management, strong mentality, intelligence, and problem solving skill. This is answered by case study research with qualitative approach using data collection through observation, interview, documentation, and focus grup discussion involving civitas academic of Islamic Religious Education Program of UIN Sunan Ampel Surabaya and sources from practitioners and scholars. The collected data are analyzed through the Miles & Huberman interactive analysis model with a data collection scheme, data condensation, data display, and conclusion. The results of the study indicate that there are a number of edupreneurship strategies to build the independence of Islamic Education students of UIN SunanAmpel Surabaya, including; establishing an incubation center, opening access to resources, organizing guidance, holding events or programs related to edupreneurship and business competitions, recognizing edupreneur students academically, and involving alumni of edupreneurs to inspire students.Students state that the campus needs to do at least three things; providing a place for students to practice edupreneurship, assigning study programs to include edupreneurship as one of the courses and learning outcomes, and providing training, seminars, workshops and guidance related to edupreneurship.